2012
DOI: 10.1007/s12072-012-9413-0
|View full text |Cite
|
Sign up to set email alerts
|

Humoral autoimmune response heterogeneity in the spectrum of primary biliary cirrhosis

Abstract: ObjectiveTo compare autoantibody features in patients with primary biliary cirrhosis (PBC) and individuals presenting antimitochondria antibodies (AMAs) but no clinical or biochemical evidence of disease.MethodsA total of 212 AMA-positive serum samples were classified into four groups: PBC (definite PBC, n = 93); PBC/autoimmune disease (AID; PBC plus other AID, n = 37); biochemically normal (BN) individuals (n = 61); and BN/AID (BN plus other AID, n = 21). Samples were tested by indirect immunofluorescence (II… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
19
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 23 publications
2
19
0
Order By: Relevance
“…We thank Dellavance et al for their interesting comment. We agree that both their results (1) and ours (2) lend support to the hypothesis that emergence of primary biliary cholangitis (PBC) is not related to antimitochondrial antibodies (AMA) positivity per se, but rather to quantitative and qualitative escalating changes in autoreactivity and humoral response preceding the clinical phase of the disease. Although the two studies differ in terms of initial design and AMA screening methods (cytoplasmic AMA-like pattern in the ANA-Hep-2 immunofluorescence [IF] assay in the Brazilian study and IF assay on rat liver, kidney, and stomach tissue sections in the French study), both found a high proportion of AMA-positive patients with no clinical evidence of PBC (54% and 32%, respectively).…”
supporting
confidence: 86%
See 1 more Smart Citation
“…We thank Dellavance et al for their interesting comment. We agree that both their results (1) and ours (2) lend support to the hypothesis that emergence of primary biliary cholangitis (PBC) is not related to antimitochondrial antibodies (AMA) positivity per se, but rather to quantitative and qualitative escalating changes in autoreactivity and humoral response preceding the clinical phase of the disease. Although the two studies differ in terms of initial design and AMA screening methods (cytoplasmic AMA-like pattern in the ANA-Hep-2 immunofluorescence [IF] assay in the Brazilian study and IF assay on rat liver, kidney, and stomach tissue sections in the French study), both found a high proportion of AMA-positive patients with no clinical evidence of PBC (54% and 32%, respectively).…”
supporting
confidence: 86%
“…In the Brazilian study, higher titers of AMA, high-avidity anti-PDC-E2, and response to three or more antigenic cell domains were independently associated with established PBC. (1) In the French study, female sex, younger age, higher AMA titers, higher rate of AMA-positive dotting/blotting tests, and higher detection rate of PBC-specific (PBC-sp.) antinuclear antibodies (ANAs) were individually associated with definite PBC.…”
mentioning
confidence: 96%
“…It is established that AMA-M2 is more specific to PBC than to AIH (13); therefore, the AMA-M2 titer is a common test for PBC (25,26). A problem with this is that patients with AIH can still test positive for AMA-M2 (21).…”
Section: Discussionmentioning
confidence: 99%
“…reported that IgG and IgA AMA titers are positively associated with Mayo risk score in a cohort of 103 patients with PBC but none of the isotypes could be used to predict disease outcome [74]. Analysis of AMA reactivity by IIF and PDC-E2 ELISA between serum samples from AMA positive PBC patients and individuals with AMA without clinical or biochemical evidence of disease, showed that high-titer IIF-AMA and high-avidity anti-PDC-E2 were associated with established PBC [89]. In another study, the presence of intense granular staining of PDC-E2 and an autophagy marker, microtubule-associated protein-light chain 3β in damaged small bile ducts of PBC patients suggests that dysregulated autophagy together with abnormal expression of mitochondrial antigens may be involved in the bile duct pathology of PBC [90].…”
Section: Ama and Pathogenesis Of Pbcmentioning
confidence: 99%